Pengaruh Citra Aplikasi Kitabisacom terhadap Minat Donasi Generasi Milenial di Masa Pandemi Covid-19 - Erwan, Chelsea; Farid, Farid (Koneksi, 2022)
The Kitabisacom application is a well-known platform to raise funds and donate which is available in smartphone or website in Indonesia. During the Covid-19 pandemic, Indonesians experienced economic difficulties. Some were infected with Covid-19 and couldn’t pay for hospital fees. A lot of millennials use this application to make donations to those in need. To find out how the image of the Kitabisacom application affects millennial generation's interest in donations during Covid-19 pandemic and whether Kitabisacom application's image can increase millennial generation's interest in donations during Covid-19 pandemic is the purpose. The theory used is the image theory from Sumardi (2021): (dynamic, cooperative, business, character, successful, and withdrawn) and Gilchrist's theory of donation interest (2019): (attitude, norms, and behavioral intention). This study uses quantitative approach with 100 samples of @Kitabisacom Instagram followers through purposive sampling technique. From the simple linear regression test, every time there is an addition of a value or number for the influence of the Kitabisacom application image (X), there will be an increase in donation interest (Y) worth 0.443 (regression coefficient). The T-test shows the influence of the Kitabisacom application's image on the millennial generation's interest in donations during the Covid-19 pandemic. Aplikasi Kitabisacom merupakan platform untuk menggalang dana dan berdonasi yang tersedia dalam bentuk aplikasi smartphone maupun website yang terkenal di Indonesia. Selama pandemi Covid-19, sejumlah masyarakat Indonesia mengalami kesulitan ekonomi maupun terinfeksi Covid-19 dan tidak mampu membayar biaya rumah sakit. Generasi milenial menggunakan aplikasi Kitabisacom untuk menggalang dana ataupun melakukan donasi kepada yang membutuhkan. Penelitian ini ingin mengetahui apakah citra aplikasi Kitabisacom dapat meningkatkan minat donasi generasi milenial saat pandemi Covid-19. Teori yang digunakan yakni teori citra menurut Sumardi (2021) yaitu dynamic, cooperative, business, character, successful, dan withdrawn. Selain itu juga teori minat donasi oleh Gilchrist (2019) yaitu attitude, norms, dan behavioral intention. Metode penelitian yang digunakan yakni pendekatan kuantitatif serta metode survei dengan 100 sampel dari pengikut Instagram @Kitabisacom dengan non-probability sampling serta teknik purposive sampling. Dari uji regresi linear sederhana didapati bahwa setiap adanya penambahan angka atau nilai untuk pengaruh citra aplikasi Kitabisacom, maka akan terdapat kenaikan minat donasi senilai 0,443 (koefisien regresi). Uji T juga menunjukan adanya pengaruh citra aplikasi Kitabisacom terhadap minat donasi generasi milenial saat pandemi Covid-19.